2017
DOI: 10.3390/ma10091039
|View full text |Cite
|
Sign up to set email alerts
|

Compression Fracture of CFRP Laminates Containing Stress Intensifications

Abstract: Abstract:For brittle fracture behaviour of carbon fibre reinforced plastics (CFRP) under compression, several approaches exist, which describe different mechanisms during failure, especially at stress intensifications. The failure process is not only initiated by the buckling fibres, but a shear driven fibre compressive failure beneficiaries or initiates the formation of fibres into a kink-band. Starting from this kink-band further damage can be detected, which leads to the final failure. The subject of this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…During the course of this experimental research activity, a more thorough literature review was taking place that specifically targeted studies on lay-up sequence and compression strength of quasi-isotropic laminates. A paper by Leopold et al 11 addressed the same issue found in this study. In that study, 24-ply quasi-isotropic carbon/epoxy laminates with varying lay-up sequence were tested for undamaged compression, OHC and CAI strengths.…”
Section: Open Hole Compression Strength Of Face Sheetssupporting
confidence: 76%
See 1 more Smart Citation
“…During the course of this experimental research activity, a more thorough literature review was taking place that specifically targeted studies on lay-up sequence and compression strength of quasi-isotropic laminates. A paper by Leopold et al 11 addressed the same issue found in this study. In that study, 24-ply quasi-isotropic carbon/epoxy laminates with varying lay-up sequence were tested for undamaged compression, OHC and CAI strengths.…”
Section: Open Hole Compression Strength Of Face Sheetssupporting
confidence: 76%
“…The most notable increase in OHC and CAI strengths in Ref. 11 came when all of the 0° plies of the 24-ply laminate were clustered at the center of the specimen. This gave 45% higher OHC and CAI strengths.…”
Section: Methodsmentioning
confidence: 97%
“…19 Open hole-compression experiments conducted by Leopold et al. 29 established that when ply thickness could influence stress concentration than the stacking sequence, failure initiation depended mainly on the stacking sequence, due to influence of 0° ply.…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…Many works can be found in the scientific literature on modelling of in-plane stresses and damage evolution around a hole in a laminate subjected to tensile [20][21][22][23] and compressive loads [9,10,16,24]. In spite of these works, there is a necessity to continuous working in the knowledge of the problem of open-hole laminates subjected to compressive loads.…”
Section: Introductionmentioning
confidence: 99%